2008
DOI: 10.1016/j.febslet.2008.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transcriptional corepressor activity of prospero‐related homeobox protein (Prox1) by SUMO modification

Abstract: Prospero-related homeobox protein (Prox1) plays essential roles in the development of many tissues and organs. In the present study, we show that Prox1 is modified by the small ubiquitin-like protein SUMO-1 in cultured cells. Mutation analysis identified at least four potential sumoylation sites within the repression domain of Prox1. Our data indicate that sumoylation of Prox1 reduces its interaction with HDAC3 and as a result downregulates its corepressor activity. These findings suggest that sumoylation may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
3
26
0
1
Order By: Relevance
“…This work established that Prox1 expression is also controlled at the posttranscriptional level, complementing previous studies showing that Prox1 activity is modulated at the posttranslational level by sumoylation (66,53). Ectopic expression of miR-181 or miR-31 in cultured LECs reduced Prox1 levels, resulting in the reversion of the LEC phenotype toward a BEC identity.…”
Section: Maintenance Of Lymphatic Endothelial Cell Identitysupporting
confidence: 82%
“…This work established that Prox1 expression is also controlled at the posttranscriptional level, complementing previous studies showing that Prox1 activity is modulated at the posttranslational level by sumoylation (66,53). Ectopic expression of miR-181 or miR-31 in cultured LECs reduced Prox1 levels, resulting in the reversion of the LEC phenotype toward a BEC identity.…”
Section: Maintenance Of Lymphatic Endothelial Cell Identitysupporting
confidence: 82%
“…In addition, we have identified the sumoylation site on this homeodomain transcription factor and suggest that sumoylation increases the transcriptional activity of Prox1. While preparing the results of our study for submission, we found that Shan et al had also reported that sumoylation at K556 of Prox1 reduced its interaction with histone deacetylase 3 and attenuated its transcriptional corepressor activity (Shan et al, 2008). However, the biological function of mutant Prox1 was not addressed in their study.…”
Section: Discussionmentioning
confidence: 71%
“…6(a), in vitro-translated Prox1 could be pulled down specifically by HNF-1 (lane 3). In HEK293 cells, which lack endogenous Prox1 expression (Shan et al, 2008), coexpressed FLAG-HNF-1 and HA-Prox1 were coimmunoprecipitated using anti-FLAG antibody, and coexpressed FLAG-HNF-1 and HA-Prox1 were co-immunoprecipitated by using anti-HA antibody (Fig. 6b).…”
Section: Prox1 Interacts Directly With Hnf-1mentioning
confidence: 98%